Do energy intensity reduction targets promote renewable energy development? Evidence from partially linear functional-coefficient models - Tao Ge; Yating Ge; Shuowan Lin; Jianhua Ji (Energy Strategy Reviews, 2023)
Energy intensity reduction targets can reduce fossil fuel consumption and excessive pollution emissions by developing renewable energy, as some existing studies suggest. Nonetheless, the contradiction that China's ecological environment has still been severely damaged after setting energy intensity reduction targets reminds us to reexamine the previous nexus. This study investigates how energy intensity targets affect renewable energy development at different economic levels by applying a partially linear functional coefficient model with panel data collected from 30 provinces in China during 2006–2019. The results suggest that renewable energy can be promoted by energy intensity reduction targets only when economic development levels lie between 18434 yuan (about 2673 dollars) and 87427 yuan (about 12677 dollars). The promoting effect has disappeared in most of China's developed eastern provinces, including Tianjin, Guangdong, Beijing, Fujian, Zhejiang, Shanghai, and Jiangsu. However, R&D intensity targets can serve as an alternative tool for energy intensity reduction targets in the abovementioned provinces, as they produce a significant effect on advancing renewable energy consumption, especially as such an effect gradually increases after economic development levels reach 37956 yuan (about 5504 dollars). These results indicate that policymakers should adopt target management policies and tools tailored to local conditions to develop renewable energy.